Pyrolyzed Polyaniline–Graphene Nanosheets with Enhanced Lithium‐Storage Properties: Preparation and Characterization - Wang, Yong‐Chen; Zhu, Bi‐Yu; Ni, Jiang‐Feng; Zhang, Li; Wang, Hai‐Bo; Gao, Li‐Jun (ChemElectroChem, 2014)
Pyrolyzed polyaniline–graphene nanosheets (PA–GNS) are examined as a lithium‐storage material. The PA–GNS composite is synthesized through heat treatment of polyaniline–graphite oxide precursors under a H2/Ar atmosphere at 850 °C. Scanning and transmission electron microscopies, X‐ray diffraction, Raman spectroscopy, and X‐ray photoelectron spectroscopy are employed to characterize the prepared PA–GNS composite in comparison with pristine graphene nanosheets (GNS). Galvanostatic charge/discharge experiments show that PA–GNS exhibits an improved rate and cycle capability at both 25 and 55 °C. It is also found from electrical resistivity tests and electrochemical impedance spectroscopy measurements that the PA–GNS composite demonstrates a higher vertical electronic conductivity and lower charge‐transfer resistance than GNS, and it is concluded that modifying GNS with pyrolyzed polyaniline is an effective way to enhance the rate capability and cyclability of GNS. Pyromania: Pyrolyzed polyaniline–graphene nanosheets (PA–GNS) are studied as a lithium‐storage material. High‐magnification transmission electron microscopy images of the PA–GNS composite (see figure) show distinguished areas of both pyrolyzed polyaniline (PANI) and graphene nanosheets (GNS).